2015
DOI: 10.22226/2410-3535-2015-2-170-174
|View full text |Cite
|
Sign up to set email alerts
|

The effect of warm deformation by abc-pressing method on mechanical properties of titanium nickelide

Abstract: Исследовано влияние температуры на предел прочности (σ uts ) и удлинение до разрушения (δ) при растяжении образ-цов никелида титана (50.2 ат.% Ni) с исходной крупнозернистой структурой и структурами после abc-прессования при 873К (сплав 1, истинная деформация е = 2.2) и после прессования с понижением температуры в последователь-ности 873К→673К (сплав 2, е = 4.2). Размер зёрен в образцах сплава 1 (2-40 мкм) меньше, чем в исходных образцах (20-70 мкм). Образцы сплава 2 имели субмикрокристаллическую структуру (зё… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…It was also shown that warm ECAP, in contrast to other MPD methods that are predominantly deformable by structural mechanism, is most preferable for the formation of a UFG structure, due to the predominance of the dynamic recrystallization mechanism [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Another similar method of grain-size refinement of the grain structure of titanium alloys is warm abc-pressing [ 52 ]. We have shown that uniaxial hot-pressing can also be effective for refinement of the grain structure in CG copper alloys [ 46 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that warm ECAP, in contrast to other MPD methods that are predominantly deformable by structural mechanism, is most preferable for the formation of a UFG structure, due to the predominance of the dynamic recrystallization mechanism [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Another similar method of grain-size refinement of the grain structure of titanium alloys is warm abc-pressing [ 52 ]. We have shown that uniaxial hot-pressing can also be effective for refinement of the grain structure in CG copper alloys [ 46 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…The regularities and features of microstructure evolution in TiNi-based alloys under the action of SPD at 623-773 K are studied in a number of works: [9][10][11][12][13][14][15][16][17][18][19][20][21] after ECAP and [4,5,22,23] after abc pressing. The effect of grain-subgrain structure refinement on the mechanical and inelastic properties of these alloys after ECAP was studied in [9][10][11][12][13][14][15][16][17][18][19][20][21] and after abc pressing in [22][23][24][25][26]. It was found that these methods can achieve a refinement of the grain-subgrain structure up to 100-500 nm, depending on the pressing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been established that samples of these alloys with an average grain-subgrain structure of 250-300 nm demonstrate an ultimate tensile strength of up to 1200 MPa, and the plasticity reaches 50-60%. In [1,8,14,15,[22][23][24][25]27], the effect of ECAP and abc pressing on the martensitic transformation (MT) temperatures in TiNi-based alloys was studied. The MT temperatures during the cooling and heating of samples of these alloys decrease by 20 degrees or more after ECAP at 623-773 K [1,8,14,15,27], and after abc pressing, they either do not change or change only slightly [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Research data are also available on the grain-subgrain structure of Ti 49.8 Ni 50.2 specimens exposed to abc pressing (multi-axial forging) with their true strain set from 2.2 to 1.5 or equal to ≈3.6 at each step of the strain temperature successively decreased from 873 K to 573 K [15][16][17][18]. Actually, such pressing conditions mean that each temperature step of abc pressing is applied to specimens with a different initial grain-subgrain structure.…”
Section: Introductionmentioning
confidence: 99%